Предмет: Математика, автор: KatUss

пожалуйста срочно.......​

Приложения:

Ответы

Автор ответа: khodanovich21
0

Покрокове пояснення:

-8+(-9)=-8-9=-17

-9*4=-36

-22+16=16-22=-6

-81/(-9)=9

-9-7=-16

-8+13=13-8=5

-5*(-4)=20

6-13=-7

-23-(-8)=-23+8=-15

42/(-7)=-6

4-(-27)=4+27=31

(-4)*(-4)=16

-0,5+0,8=0,8-0,5=0,3

-\frac{3}{10} -\frac{2}{10} =-\frac{5}{10} =-\frac{1}{2}

-2*(-\frac{3}{4} )=\frac{3}{2} =1\frac{1}{2} =1,5

-2*(-2)*(-2)=-8

(-8)^{2} =64

(-\frac{1}{3})^{2}  =\frac{1}{9}

Похожие вопросы